2015
DOI: 10.1021/mp500840z
|View full text |Cite
|
Sign up to set email alerts
|

GMI, an Immunomodulatory Protein from Ganoderma microsporum, Potentiates Cisplatin-Induced Apoptosis via Autophagy in Lung Cancer Cells

Abstract: Cisplatin-based therapy is common in the treatment of several types of cancers, including lung cancers. In our previous study, GMI, an immunomodulatory protein cloned from Ganoderma microsporum, induced a cytotoxic effect in lung cancer cells via autophagy. The aim of this study is to examine the role of GMI in enhancing cisplatin-mediated cell death. On the basis of MTT assay and Combination Index, GMI and cisplatin cotreatment induced a synergistic cytotoxic effect. GMI and cisplatin-induced apoptosis was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…It is worth noting that the highest expressions of p21 proteins in both GMIP concentration treatments all occurred earlier than caspase activation, indicating the sequential activation in the GMIP pathway from p21 to caspases. It is reported that GMIP induced lung cancer cells go through autophagic cell death . However, in UC cells, the expression level of the regulator protein of switching from autophagy to apoptosis, cleaved Beclin‐1 (50, 37, 35 kDa) were not shown after GMIP treatment (Figure C, 1st row).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…It is worth noting that the highest expressions of p21 proteins in both GMIP concentration treatments all occurred earlier than caspase activation, indicating the sequential activation in the GMIP pathway from p21 to caspases. It is reported that GMIP induced lung cancer cells go through autophagic cell death . However, in UC cells, the expression level of the regulator protein of switching from autophagy to apoptosis, cleaved Beclin‐1 (50, 37, 35 kDa) were not shown after GMIP treatment (Figure C, 1st row).…”
Section: Resultsmentioning
confidence: 87%
“…It is reported that GMIP induced lung cancer cells go through autophagic cell death. 19 However, in UC cells, the expression level of the regulator protein of switching from autophagy to apoptosis, cleaved Beclin-1 (50, 37, 35 kDa) were not shown after GMIP treatment ( Figure 3C, 1st row). Moreover, autophagy marker LC3B-II did not show a remarkable increase after GMIP treatment ( Figure 3C, 2nd row), so we suggested the cell death caused by GMIP was mainly through programmed apoptosis rather than autophagy.…”
Section: Gmip Induces Apoptosis Not Autophagy Through Both Extrinmentioning
confidence: 91%
See 2 more Smart Citations
“…Increasing lines of evidences have showed that both G. lucidum (Tang et al, 2006;Loganathan et al, 2014;Hsin et al, 2015) and soybean isoflavones (Kurahashi et al, 2007;Li et al, 2012b) have antitumor activity. In this study, for the first time, the transformation of soybean isoflavones was performed using the homogenate of G. lucidum, and the genistein contents could reach (703.21±4.35) mg/g, with transformed rates of 96.63% and 87.82% of daidzein and genistein, respectively.…”
Section: Discussionmentioning
confidence: 99%